PERBANDINGAN KINERJA PENJUALAN ANTARA PRODUK BARU DAN PRODUK LAMA DALAM PERSPEKTIF PENGELOLAAN MODAL KERJA DAN PROFITABILITAS - Awab Hapidin; Bintang Bagas Alfian; Dloefatul Lailiyah; Safitri Putri Derajat (Desanta Publisher, 2025)
This study aims to compare the sales performance between new products and old products from the perspective of working capital management and profitability. This study involves two independent variables: working capital management and profitability, and one dependent variable: sales performance of new and old products. The research object is companies that market both new and old products in the manufacturing industry. A sample of 60 respondents was selected using the purposive sampling technique. Data were collected through the distribution of questionnaires to company financial managers. Data analysis was performed using the multiple linear regression method processed through the SPSS version 25 program. Based on the results of the study, it was found that: 1) Working capital management has a significant effect on the sales performance of both new and old products; 2) Profitability has a significant effect on the sales performance of both new and old products; 3) Working capital management and profitability simultaneously have a significant effect on the sales performance of both new and old products; 4) Working capital management and profitability of old products show more stable sales performance compared to new products. From these findings, it can be concluded that working capital management and profitability play an important role in improving the sales performance of both new and old products, with profitability being the dominant factor influencing the sales success of old products.